A magnetic disturbance index for Mercury's magnetic field derived from MESSENGER Magnetometer data. (23rd September 2013) - Anderson, Brian J.; Johnson, Catherine L.; Korth, Haje
<x xml:space="preserve">Abstract</x> [1] We present a magnetic disturbance measure for Mercury derived from MESSENGER Magnetometer data. Magnetic field fluctuations were computed in three period bands: 0.1–2 s, 2–20 s, and 20–300 s. From these, we determined log average magnetic variability versus latitude and local time in Mercury's magnetosphere. The quietest regions are the southern tail lobe and the nightside poleward of 30° magnetic latitude, and the most disturbed regions are near magnetopause boundaries and the magnetospheric cusp. We used ratios at each location between the mean disturbance and that observed on each pass to compute normalized measures of magnetic disturbance for each orbit. Composite disturbance indices incorporate disturbance levels in all three bands. Percentile ranking of the composite indices provides a quantitative basis for selecting data from quiet to disturbed conditions.